Soundscape Optimization in Nursing Homes Through Raising Awareness in Nursing Staff With MoSART+ - Kosters, Janouk; Janus, Sarah I. M.; Van Den Bosch, Kirsten A.; Zuidema, Sytse; Luijendijk, Hendrika J.; Andringa, Tjeerd C. (Frontiers in Psychology, 2022)
Introduction Soundscapes in nursing homes are often suboptimal for residents. This can cause them feeling anxious and unsafe, or develop behavioral and psychological problems. Residents with dementia cannot adapt nursing home environments to their needs due to cognitive and physical limitations. It is up to the staff of psycho-geriatric wards to improve the soundscape. We evaluated the effect of the sound awareness intervention Mobile Soundscape Appraisal and Recording Technology (MoSART+) on soundscapes in nursing homes. Methods The MoSART+ intervention was carried out in four nursing homes and took three months in each home. The MoSART+ intervention involved training ambassadors, assessing the soundscape with the MoSART application by the nursing staff to raise their sound awareness on random time points, discussing the measurements, and implementing micro-interventions. Soundscapes were assessed from 0 to 100 on four attributes: pleasantness, eventfulness, complexity, and range of affordances. Based on these scores, soundscapes were classified in four dimensions: calm, lively, boring, and chaotic. Nursing staff graded the environment on a scale of 0 to 10. T-test and Z-tests were used to analyze data. Results Staff recorded 1882 measurements with the MoSART app. ‘People’, ‘music, TV, and radio’, and ‘machines and appliances’ were the most prevalent sound sources before and after the implementation of micro-interventions. Post-implementation of micro-interventions, soundscapes were pleasant (median 69.0; IQR 54.0-81.0), of low complexity (33.0; 18.0-47.0), uneventful (27.0; 14.0-46.5), and gave moderate affordances (50.0; 35.0-67.0). Changes in attributes were statistically significant (p<.01). The proportion of the dimension calm increased (z = 12.7, p<.01), the proportion of chaotic decreased (z = 15.0, p<.01), and the proportion of lively decreased not statically significant (z = 0.68, p = 0.79). The proportion of boring was unchanged. The proportion of grades ≥6 increased after implementation of the micro-interventions (z = 15.3, p<.01). The micro-interventions focused on removing or reducing disturbing sounds and were unique for each nursing home. Discussion The MoSART+ intervention resulted in a statistically significantly improvement of soundscapes, and more favorable evaluations of the nursing staff. The intervention empowered staff to adapt soundscapes. Nursing homes can improve soundscapes by raising sound awareness among staff.